2022
DOI: 10.3390/jcm11092640
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Rich Plasma Injections for Knee Osteoarthritis Treatment: A Prospective Clinical Study

Abstract: Background: The aim of this prospective study was to evaluate the efficacy and safety of Platelet Rich Plasma (PRP) injections in patients affected by knee osteoarthritis (KOA). An autologous blood product containing a high percentage of various growth factors (GFs), cytokines and modulating factors as PRP has shown promising results in achieving this goal. Methods: One hundred and fifty-three patients (72 males, mean age 59.06 ± 8.78, range 40–81 years old) from January 2018 to January 2020 received three con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The effects of PRP on pain reduction have been previously observed in other studies and several authors have reported the analgesic properties of platelets [ 44 , 45 ]. Postoperative pain was mainly induced by inflammation [ 46 ].…”
Section: Discussionmentioning
confidence: 63%
“…The effects of PRP on pain reduction have been previously observed in other studies and several authors have reported the analgesic properties of platelets [ 44 , 45 ]. Postoperative pain was mainly induced by inflammation [ 46 ].…”
Section: Discussionmentioning
confidence: 63%
“…Another significant clinical trial carried out by Moretti. L et al concluded that although there was noteworthy pain reduction in people who were diagnosed with KOA, there were no radiographic changes reflected (39). Recent studies have also indicated an increased efficacy of PRP in Ahlba ck grades I and II as compared to more severe OA (40).…”
Section: Discussionmentioning
confidence: 99%
“…PDGF plays a crucial role in cell proliferation and angiogenesis, while TGF-β is renowned for its involvement in cell differentiation and the synthesis of extracellular matrix components. Conversely, IGF exerts potent effects on cellular metabolism and tissue development [ 7 ]. The synergistic action of these growth factors is fundamental to the therapeutic mechanisms of PRP.…”
Section: Reviewmentioning
confidence: 99%